Nunatsiavut, ‘Our beautiful land’: Inuit landscape ethnoecology in Labrador, Canada - Cuerrier, Alain; Clark, Courtenay; Dwyer-samuel, Frédéric; Rapinski, Michel (Botany, 2022)
For Inuit in the subarctic transition zone of northeastern Canada, an intimate knowledge of the environment and local biodiversity is crucial for successful traditional activities. This study examines what kinds of landscape features and habitats Inuit of Nunatsiavut recognize and name. During interviews, community members (mostly Elders) were shown photographs from the region, and were asked to describe and name salient types of places in Labrador Inuttitut. The most frequently reported geographical units dealt with the region’s topography (e.g., ‘mountain’, ‘island’, ‘flat-place’), hydrology (e.g., ‘river’, ‘bay’), and superficial characteristics (e.g., ‘bedrock’, ‘permanent snow patch’). Ecological considerations were also prominent, such as plant associations and animal habitats (e.g., ‘shrubby-place’, wetland’, ‘caribou-return-to-place’). Areas were often characterized by a dominant species or substrate type, being named using the plural form of the species/substrate (e.g., napâttuk ‘tree’/ napâttuit ‘forest’, siugak ‘sand’/siugalak ‘sandy-area’). Some types of places reported by Inuit were significant mainly for traditional activities (e.g., ‘berry-patch’, ‘seal-place’, ‘dry-wood-place’, ‘danger-place’), aiding navigation and resource finding. Integrating Inuit conceptions of ecosystems and their component landscape units with those of contemporary science can improve our understanding of subarctic ecology, benefit climate change adaptation strategies and Inuit language/culture conservation initiatives.